The Relationship Between Nursing Students' Medical Error Tendency and Personality Types and Assertiveness: A Cross-Sectional Study. - SAYGILI DÜZOVA, Ülkü; KILIÇ, Mustafa; KOÇAK, Ayyüce Tuba; AKGÖZ, Nurseza (Turkiye Klinikleri Journal of Nursing Sciences, 2025)
Objective: The aim of this study is to assess the relationship between nursing students' medical error tendency levels, their personality types, and their assertiveness levels. Material and Methods: The study is a descriptive and cross-sectional study. It was conducted between March-June 2023 at the faculty of nursing of a state university. A total of 193 undergraduate students participated in the study. Data were collected using the Personal Information Form, Nursing Medical Error Proneness Scale, Type A Personality Scale and Rathus Assertiveness Inventory. The data were analyzed by calculating the frequency, percentage, mean and standard deviation and by using correlation analysis. Results: During clinical practice, 23.8% of the students were found to have sharp object injuries, 24.4% to have contact with patient blood/contaminated material. The average Type A Personality score of the students was 73.79±15.57 and the average Assertiveness score was 11.32±23.47. Students with high Assertiveness scores tended to make medical errors (p<0.05). A negative significance was determined between Assertiveness and the Type A Personality Scale timing sub-dimension (p<0.05). Conclusion: It was determined that the students had high type A personality scores and low assertiveness scores. It was observed that students with type A personality traits were more prone to medical errors due to higher stress levels and students who followed field-specific scientific publications were less likely to make medical errors.